Correlation of radiation dose and activity with clinical outcomes in metastatic colorectal cancer after selective internal radiation therapy using yttrium-90 resin microspheres. Issue 10 (October 2018) - Badiyan, Shahed; Bhooshan, Neha; Chuong, Michael D.; Sharma, Navesh; Akhter, Nabeel; Etezadi, Vahid; Hausner, Petr; Kudryasheva, Svetlana; Kaiser, Adeel; Becker, Stewart; Guerrero, Mariana; Yi, Byong Y.
Abstract : Purpose: Yttrium-90 ( 90 Y)-resin microspheres are prescribed using activity. We evaluated overall survival (OS) and radiographic tumor response after selective internal radiation therapy (SIRT) with resin microspheres in patients with liver metastases from colorectal cancer. Patients and methods: We retrospectively reviewed 60 metastatic colorectal cancer patients treated at our institution with SIRT using 90 Y-resin microspheres. Each patient underwent pre-SIRT MRI or computed tomography imaging of the liver with intravenous contrast. Patients underwent post-treatment imaging at 2–3-month intervals with response assessed according to unidimensional Response Evaluation Criteria in Solid Tumors (RECIST) criteria as well as published three-dimensional volumetric criteria. We then related the prescribed activity established by the body surface area method and the corresponding prescribed dose to radiographic treatment response and OS. Results: The median follow-up after the first SIRT treatment was 8.9 months. The mean prescribed activity and the prescribed dose were 26.6 mCi and 52.8 Gy, respectively. OS was not significantly associated with either prescribed activity or prescribed dose. Prescribed dose was also not related to response. However, a significant relationship was found between a higher prescribed activity and an improved radiographic response by RECIST ( P =0.04) at the second follow-up. Conclusion: The prescribed activity of 90 Y-resin microspheres may be correlated with radiographic response by RECIST criteria at 4–6 months post-treatment. For a more accurate prediction of response, a valid dose calculation model based on post- 90 Y PET dosimetry is likely needed given the heterogeneous dose delivery seen in SIRT.